The effects of atorvastatin on oxidative stress in L-NAME-treated rats. (October 2013) - Sozer, Volkan; Uzun, Hafize; Gelisgen, Remise; Kaya, Mehmet; Kalayci, Rivase; Tabak, Omur; Arican, Nadir; Konukoglu, Dildar
Abstract Objectives. Current evidence suggests that the beneficial vascular effects of statins are not limited to the statins' lipid-lowering properties; these drugs can also improve vascular endothelial cell function. Nω-nitro-l-arginine methyl ester (L-NAME) is a potent synthetic nitric oxide inhibitor, and long-term oral L-NAME treatment is used to induce vascular lesions in experimental animal models. Methods. We determined the effects of statins on protein carbonyl (PCO), lipid hydroperoxides (LHP), oxidized low-density lipoproteins (ox-LDL) and antioxidants such as paraoxonase 1 (PON1) and total thiols (T-SH) in long-term L-NAME-treated rats. Adult male Wistar rats were divided into three groups, namely, control, L-NAME-treated (1 mg/mL in drinking water for three weeks), and atorvastatin plus L-NAME-treated (4 mg/kg/day atorvastatin for 1 week during the third week of L-NAME treatment) groups. Results. In the L-NAME group, the ox-LDL, LHP and PCO were higher and the PON1 and T-SH were lower than the concentrations observed for the controls. When compared with the L-NAME group, the L-NAME plus atorvastatin group had significantly lower ox-LDL and LHP and higher PON1 activities. Additionally, the elevated total cholesterol (TC) and low-density lipoprotein-C (LDL-C) in the L-NAME group were decreased by atorvastatin administration. TC and LDL-C were positively correlated with ox-LDL and LHP and negatively correlated with PON1 in all groups. High-density lipoprotein-C (HDL-C) was negatively correlated with ox-LDL. Conclusion. PON1 prevents LDL oxidation and inactivates LDL-derived oxidized phospholipids; its activity showed a pronounced decrease in the L-NAME treatment group and was increased in the atorvastatin group. Based on our findings, we concluded that the atorvastatin had HDL-related antioxidant activity as well as lipid-lowering properties.